1982
DOI: 10.1097/00000658-198209000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Depressed Immune Response in Burn Patients

Abstract: Recent experimental evidence has suggested that circulating suppressor leukocytes play an important role in mediating the suppression of immunity seen in burn patients. In order to shed further light on the relationship between suppressor cells and depressed cellular immunity 22 patients were studied (mean age 37) who had suffered severe burns of greater than 30% body surface area. Simultaneous studies were performed on 14 control laboratory personnel (mean age 32). Monoclonal antibodies were used to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Lysosomal enzymes and free oxygen radicals are released after hypoxia, leading to the development of intestinal mucosal lesions, a decrease in mucus secretion, deterioration of intestinal barrier function, and finally BT. [23][24][25] Accordingly, our group 2 had significantly greater BT and significantly worse mucosal damage than the other groups. Sepsis and septic complications increase mortality and morbidity after thermal injury.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Lysosomal enzymes and free oxygen radicals are released after hypoxia, leading to the development of intestinal mucosal lesions, a decrease in mucus secretion, deterioration of intestinal barrier function, and finally BT. [23][24][25] Accordingly, our group 2 had significantly greater BT and significantly worse mucosal damage than the other groups. Sepsis and septic complications increase mortality and morbidity after thermal injury.…”
Section: Discussionmentioning
confidence: 57%
“…Sepsis and septic complications increase mortality and morbidity after thermal injury. 2,10,11,24,26 Recent studies on immunoprotective enteral diets have shown that they provide both metabolic and immunological support for such patients. [9][10][11]27 Choudhry et al suggested that a diet enriched with immunocompounds, such as arginine, fish oil, nucleotides, and glutamine can prevent T-cell dysfunction after thermal injury.…”
Section: Discussionmentioning
confidence: 99%
“…The universal control pair was retained through out the experiment so that in sequential tests lympho cytes from experimental pigs were always mixed with the same universal control pair. Mixed lymphocyte cultures were prepared as follows: the technique for three-way MLC was based on the methods of Miller and Baker [14], Mclrvine et al [15], and Thurman et al [ 16]. Fresh lymphocytes were always used as cryopreserved pig lymphocytes do not function as well as fresh cells in the MLC [17].…”
Section: Mixed Lymphocyte Culturementioning
confidence: 99%